2010
DOI: 10.1111/j.1365-3040.2010.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Separating parental environment from seed size effects on next generation growth and development in Arabidopsis

Abstract: Plant growth and development is profoundly influenced by environmental conditions that laboratory experimentation typically attempts to control. However, growth conditions are not uniform between or even within laboratories and the extent to which these differences influence plant growth and development is unknown. Experiments with wild-type Arabidopsis thaliana were designed to quantify the influences of parental environment and seed size on growth and development in the next generation. A single lot of seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 31 publications
4
76
0
Order By: Relevance
“…Some authors only found effects of the maternal environment (for example, Galloway et al, 2009), whereas others have found the opposite (for example, Halpern, 2005). Most frequently, however, both factors have been found to significantly affect mean SM (for example, Stoehr et al, 1998;Elwell et al, 2011). Our results agree with these studies, and clearly show a strong genetic component in SM as well as a large influence of the maternal environment (Table 2, Figure 1).…”
Section: Sm Variationsupporting
confidence: 82%
See 2 more Smart Citations
“…Some authors only found effects of the maternal environment (for example, Galloway et al, 2009), whereas others have found the opposite (for example, Halpern, 2005). Most frequently, however, both factors have been found to significantly affect mean SM (for example, Stoehr et al, 1998;Elwell et al, 2011). Our results agree with these studies, and clearly show a strong genetic component in SM as well as a large influence of the maternal environment (Table 2, Figure 1).…”
Section: Sm Variationsupporting
confidence: 82%
“…These epigenetic changes may persist over the whole life cycle, and there is even evidence that they could be transmitted across generations (Boyko et al, 2010). In contrast, when maternal influence is through the mediation of SM it tends to be more pronounced during the first stages of seedling development, becoming less significant as the seedling ages (Elwell et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…4) was reasonable because the C. virosa dispersal strategy is floating and spreading through water flooding (Mulligan and Munro, 1981). But, the interpretation of positive correlation between germination (%) and water level was complicated due to the influence of seed weight on germination and a correlation between seed weight and site moisture (Schütz and Rave, 1999;Elwell et al, 2011).…”
Section: Variation In Dormancy and Germination Responsementioning
confidence: 99%
“…This could have a number of explanations. First, it is already known that early life history at the embryo stage can influence auxin signaling and ultimately result in differential growth and biomass accumulation (Paul-Victor et al, 2010;Elwell et al, 2011). As growth is an iterative process built on all events that occurred before a given time point, any early life event has the potential to influence the organism even after the event has passed.…”
Section: What Rhizosphere Element Does the Lateral Root Constraint Almentioning
confidence: 99%